Exploration of the parameters for Leagile practices in food supply chain in India - Papri Ray,Dr R Duraipandian (International Journal of Advanced Science and Technology, 2020)
In the global economy, India has increased agricultural imports and exports to other countries. India, being an agricultural power house has most of agricultural practices to be traditional. Compared to previous years, in the present scenario, the growth is not prominent when compared to that of other countries. Across the country, there are different practices followed by farmers which may not add any value to the process but the costs incurred by farmers for cultivation is too high and margin they get is too low. This may be mainly due to productivity of agricultural practices which produces waste before it reaches consumer. The paper primarily focuses in identifying and eliminating non-value added activities and standardize processes to increase effective farm yield